Investigating the Evolution of Cloud Computing: Research Perspectives (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Cloud computing is an economical and powerful tool for small businesses, especially in developing countries. It offers a scalable solution for enterprise resource planning, supply chain management, customer relationship management, healthcare applications, and mobile apps that can reach many users. In this paper, we examine the various concepts associated with cloud computing. Leveraging our experience with different clouds, we explore clouds from technical and business perspectives. We highlight some of the opportunities in cloud computing, emphasizing the importance of cloud technology. This paper provides detailed information about the features, uses, and practical applications of cloud computing.